Anticyphon gen. nov., a new genus of Scirtidae (Coleoptera: Scirtoidea) inhabiting high altitude Andean cloud forests and páramo formation - Ruta, Rafał (Zootaxa, 2016)
A new genus of Scirtidae is described to accommodate six newly described species distributed in the northern part of the Andes. Three species are described from Ecuador (Anticyphon davidsoni sp. nov., A. ecuadorensis sp. nov., A. paramoensis sp. nov.), two from Peru (A. oyonensis sp. nov., A. peruvianus sp. nov.), and a single one from Colombia (A. santanderensis sp. nov.). Morphological characters are illustrated with focus on hind wings, mouthparts and male genitalia. An identification key to species is provided.